Lean System: Analysis of scientific literature and identification of barriers for implementation from a bibliometric study - Lobato, Christiane Greijal; Cristino, Talita Mariane [UNESP]; Neto, Antônio Faria [UNESP]; Branco Costa, Antônio Fernando (FapUNIFESP (SciELO), 2021)
This article presents a bibliometric analysis on the Lean System over the period ranging from 2006 to 2017, showing the evolution of the publications over the years, the number of publications per country, the main journals, the most prolific authors, the most used keywords, and eventually barriers for the implementation of the Lean System. The greatest growth of publication rate occurred from 2014 to 2015. The countries with the most contribution have been the United Kingdom, the United States, and Sweden. The publications have been concentrated primarily in twelve journals. The bibliometric map of keywords presented them grouped into six clusters. Several underlying factors like technical and managerial aspects, planning, and leadership can explain the main barriers for the implementation of the Lean System. According to the literature, the understanding of such barriers is the best way to reduce the implementation-time and reach profitability and competitiveness. Therefore, the main contribution of this work is to make the evolution and importance of publications in this area are better known, helping organizations in the knowledge of the Lean System implementation barriers present in the literature, and in reformulating the curricula of undergraduate and postgraduate in disciplines related to Lean System. Finally, a future scientometric analysis on the subject is suggested, covering the analysis of evolution of publications, scientific journal, and authors distributions, by means of bibliometric laws, like those by Price, Bradford and Lotka, respectively.
Sistema Lean: Análise da literatura científica e identificação de barreiras para implementação a partir de um estudo bibliométrico
Keywords: Barriers; Barriers for Lean implementation; Bibliometric methods; Lean implementation; Lean system